Evaluation of Oxidative Stress with Thyroid Function in Growth Hormone-deficient Children from Misan Government ,Iraq. - Mohammed Abdul-Mounther; Mohammed Abed Draweesh; Farah Mjbaal; Mahdi Murshd ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
Aim: Growth hormone deficiency (GHD) is a complex endocrine syndrome, which is most commonly known to affect the pediatric population. However, adults also suffer from GHD, and it is often seen as part and parcel of the aging phenomenon. We aimed to investigate the levels and relationships of antioxidants, lipid peroxidation and thyroid function with altogether in growth hormone deficiency . Method: This study was conducted to measure a group of hormones related with infected individuals with the shortage of the growth hormone by studying 57 sample Which represents patient groups were ( 38 boys and 19 girls ) divided in to two groups according to age Group (1): consist of 26 patients (boys 14 and 12 girls ) their aged ranged from 2 to 8 years and Group (2) Consisted of 31 patients ( 24 boys and 7 girls ). Their ages ranged from 9 to 16 years in comparison with 50 samples taken from normal individuals as a control group. The concentration of hormones has been measured were human Growth hormone (hGH) Total Triidothyronin(TT3), Total Thyroxin (TT4),Free Thyroxin (FT4)Thyroid Stimulating (TSH), serum malondialdehyde (MDA) ,Vitamin C , Erythrocyte superoxide dismutase (SOD) activity, plasma Total antioxidant capacity (TAC)